Perforated solitary mid-rectal diverticulum diagnosed with colonoscopy: a case report and literature review - Nikolovski, Andrej; Avramoski, Vladimir; Gjinoska, Klaudia; Kostovska, Irena; Stoicovski, Emil; Mitrev, Zan (Oxford University Press (OUP), 2025)
Rectal diverticulum is an exceedingly rare clinical entity, typically occurring as a solitary lesion or, less frequently, as up to three diverticula. Its development is often associated with underlying conditions such as obstructive defecation syndrome, rectal malignancy, pelvic floor weakness, chronic rectal impaction, obesity, or infection-related muscular atrophy. Although uncommon, rectal diverticulitis represents a surgical emergency requiring timely recognition and management. In this case, a female patient presented with rectal bleeding and secondary anemia. During the clinical course, the patient developed pelvic sepsis secondary to rectal diverticulitis. Appropriate surgical intervention, combined with antimicrobial therapy and supportive management, led to a favorable outcome. Rectal diverticulitis is a rare but potentially life-threatening condition. Awareness of this entity and early diagnosis are essential to prevent severe complications such as perforation and pelvic sepsis. This case highlights the importance of considering rectal diverticulum in the differential diagnosis of lower gastrointestinal bleeding and pelvic infections.
Keywords: rectal diverticulum; intestinal perforation; diverticulitis; abscess; Hartmann’s procedure